An Investigation into the Logic Textbooks Written in Accordance with the 2009 Logic Curriculum - Duman, Ekrem Ziya; Aslan, Gamze (Asian Journal of Education and Training, 2019)
Textbooks have attained an essential position with the student-centered approach. Accordingly, curricula are developed based largely on constructivist approach. Since textbooks are prepared in accordance with the curriculum, they are therefore constructivist approach-oriented. As a result, textbooks are the reflection of the curriculum. The mistakes in textbooks can directly affect learning in a negative manner. Additionally, the visuals, reading texts, preparation and evaluation questions in textbooks should be on a par with the outcomes in the curriculum in regard to level and structure. In this study, three of the textbooks written in accordance with the 2009 logic course curriculum were examined in terms of physical features, distribution by units, their congruence to the curriculum, language and expression, scientific content, print-typesetting-orthography, reading texts, preparation and evaluation questions, and bibliography. From this aspect, this study is qualitative. Document review method was adopted in this study. It was discovered that the evaluation questions in the textbooks framed to measure the outcomes were under the outcome levels. To exemplify, the questions taxonomically at the evaluation level were found to be corresponding to the knowledge and comprehension levels, it was further explored that most errors were detected in the elements of print-typesetting-orthography.